Enhanced Oxidative Stress Resistance through Activation of a Zinc Deficiency Transcription Factor in Brachypodium distachyon. Issue 3 (16th September 2014) - Glover-Cutter, Kira M.; Alderman, Stephen; Dombrowski, James E.; Martin, Ruth C.
Abstract : A zinc deficiency transcription factor moderates oxidative stress resistance . Abstract: Identification of viable strategies to increase stress resistance of crops will become increasingly important for the goal of global food security as our population increases and our climate changes. Considering that resistance to oxidative stress is oftentimes an indicator of health and longevity in animal systems, characterizing conserved pathways known to increase oxidative stress resistance could prove fruitful for crop improvement strategies. This report argues for the usefulness and practicality of the model organism Brachypodium distachyon for identifying and validating stress resistance factors. Specifically, we focus on a zinc deficiency B. distachyon basic leucine zipper transcription factor, BdbZIP10, and its role in oxidative stress in the model organism B. distachyon . When overexpressed, BdbZIP10 protects plants and callus tissue from oxidative stress insults, most likely through distinct and direct activation of protective oxidative stress genes. Increased oxidative stress resistance and cell viability through the overexpression of BdbZIP10 highlight the utility of investigating conserved stress responses between plant and animal systems.